Improvements in bio-based building blocks production through process intensification and sustainability concepts. (2021) - Segovia-Hernández, Juan Gabriel; Sanchez-Ramirez, Eduardo; Ramirez-Marquez, Cesar; Contreras-Zarazúa, Gabriel
No abstract available